Enhancement of polysiloxane/epoxy resin compatibility through an electrostatic and van der Waals potential design strategy - Yuhao Liu; Ying Lin; Bin Cao; Kangning Wu; Liming Wang (Polymer Testing, 2023)
The unclear molecule structures-compatibility relationship obstructs the enhancement of compatibility between polysiloxane and epoxy resins. Herein, we reveal the molecule structures-compatibility relationship and propose a synergistic design strategy to improve compatibility. Taking three typical terminal molecular structures (-NH2 group, –OH group and epoxy group) as examples, it is found that the solubility parameter and binding energy parameter of polysiloxanes are dominated by van der Waals interaction, which is closely related to the number of terminal atoms. The –NH2 group is with the strongest electrostatic interaction due to the strong electrostatic potential and low steric hindrance. On this basis, silicone prepolymer is successfully synthetized to improve compatibility through synergistically enhancing the van der Waals interaction and electrostatic interaction by increasing the number of terminal atoms and introducing –NH2 group. Consequently, Si element is uniformly distributed in the epoxy resin with silicone prepolymer, which indicates highly compatible effects. The hydrophobicity of epoxy resin is also significantly improved about 19.03% by the silicone prepolymer. The established molecular structure-compatibility relationship and proposed synergistic design strategy open up an alternative design concept for compatibility improvement in multiphase organic polymers and can be applied in insulation, moisture-proof and other fields.